Making a Case for Infection Control at Public Places of Convenience in Accra, Ghana - Eric S Donkor; Nana Esi S. Anyen; Amos Akumwena (SAGE Publishing, 2020)
In Ghana, environmental hygiene remains a major problem and infection control measures are hardly practised, particularly outside of the hospital. To provide evidence for infection control measures at public places of convenience in Accra (capital city of Ghana), this study was performed. The aim of the study was to evaluate microbial contamination of door handles at public places of convenience in Accra and assess the public health risk. A total of 183 swab specimens were collected aseptically from door handles of public places of convenience of shops, schools, hospitals, lorry stations, churches, and markets. The samples were cultured on bacteriological media, and the isolated organisms were identified. The most prevalent bacterial agent isolated was Bacillus spp. (55.7%), followed by Staphylococcus aureus (20.2%), coagulase-negative staphylococcus spp. (17.1%), Citrobacter freundii (6.0%), Citrobacter koseri (4.4%), and Salmonella Paratyphi A (3.8%). Although in low prevalence, a wide range of enteric bacteria were isolated from door handles, accounting for 12 of the 16 isolated organisms. In conclusion, door handles of places of convenience in Accra harbour several pathogenic microorganisms, especially enteric organisms. This study highlights the need for proper disinfection of door handles of places of convenience in Accra as well as handwashing after visiting such places.